Clinical effects of switching from minodronate to denosumab treatment in patients with postmenopausal osteoporosis: a retrospective study - Masaki Kobayashi; Kenjiro Sawada; Akihiko Yoshimura; Misa Yamamoto; Aasa Shimizu; Kotaro Shimura; Naoko Komura; Mayuko Miyamoto; Kyoso Ishida; Tadashi Kimura (BMC, 2020)
Abstract Background Denosumab is a major treatment option for patients with postmenopausal osteoporosis; however, the evidence for its use is lacking. Therefore, in this 24-month retrospective study, we aimed to evaluate the effects of switching from minodronate (MIN) to denosumab in these patients. Methods Patients with postmenopausal osteoporosis either switched from MIN to denosumab (Group 1; n = 32) or continued MIN treatment (Group 2; n = 24). Bone mineral density (BMD) of the lumbar spine (L2-L4) and femoral neck was assessed at baseline and every 6 months for 24 months. Serum bone-specific alkaline phosphatase (BAP) and N-terminal telopeptide were measured at baseline, 12 months, and 24 months. Results Twenty-nine of the 32 patients (90.6%) in group 1 and all patients (24/24) in group 2 completed the 24-month follow-up. Switching from MIN to denosumab (Group 1) significantly increased lumbar BMD at 12, 18, and 24 months (6.1, 7.4, and 9.6%, respectively) and femoral neck BMD at 12, 18, and 24 months (2.8, 3.2, and 3.4%, respectively), whereas MIN continuous treatment (Group 2) showed no significant difference from baseline. Switching therapy also showed a significant decrease in serum BAP from baseline to 12 and 24 months (− 19.3 and − 26.5%, respectively) and serum NTX from baseline to 12 months (− 13.1%), whereas continuous MIN treatment failed to show any significant differences from baseline. Conclusion Switching from MIN to denosumab in patients with postmenopausal osteoporosis showed clinical benefits with regard to BMD and bone turnover markers in comparison with continuous MIN treatment. It may therefore be a valid treatment option in the clinical setting.